A factorable Banach algebra with inequivalent regular representation norm - Leinert, Michael (Proceedings of the American Mathematical Society, 1976)
An example is given of a semisimple commutative Banach algebra which factorizes but whose norm is not equivalent to the norm induced by its regular representation. This is a stronger version of the example given in [4] and it can be viewed as an example of a factorizing commutative abstract Segal algebra.